3x-4-8x+12=

Simple and best practice solution for 3x-4-8x+12= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-4-8x+12= equation:


Simplifying
3x + -4 + -8x + 12 = 0

Reorder the terms:
-4 + 12 + 3x + -8x = 0

Combine like terms: -4 + 12 = 8
8 + 3x + -8x = 0

Combine like terms: 3x + -8x = -5x
8 + -5x = 0

Solving
8 + -5x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8' to each side of the equation.
8 + -8 + -5x = 0 + -8

Combine like terms: 8 + -8 = 0
0 + -5x = 0 + -8
-5x = 0 + -8

Combine like terms: 0 + -8 = -8
-5x = -8

Divide each side by '-5'.
x = 1.6

Simplifying
x = 1.6

See similar equations:

| 15-4X=-X | | 3(x-3)+5=4(x-2)-10 | | 5ab-6ab+a= | | 2senx-cosx=-4 | | P=20+6ln(2q+1) | | 13x+15=3x+215 | | B+280= | | I=IR | | 5x+5x+130=180 | | -12+5m+10m=-2m-10-m | | 4(3x+3)=14x+11-2x+1 | | (3a-5)(2a+3)=0 | | -8=x/4+3 | | 3y=5x-y | | 5x+10=-48-7x | | 5(-3x-7)=-4(4x+9) | | 6(x-1)-5=4x+2(-3+x) | | 55-(2c+3)=4c(c+6)+c | | 7y+9=30 | | 7x-5=5(x+11)+2x-10 | | -2(m+2)=-8 | | (4x^8+11x^6-7x^2+3)-(9x^8-5x^4+8x^2-4)=0 | | 0.009(x+200)+0.06x=63 | | f(x)=10xfor | | 9c-6c=-8+11 | | 5x+6x-40=100-9x | | 45-4x*5=80 | | 8x+48=9x | | 0.5x+0.7x=1.7 | | -8=3-2(c-4)+3 | | 8+20x=x-4 | | P=50h+200 |

Equations solver categories